Structuring an Efficient Organic Wheat Breeding Program - Baenziger, P. Stephen; Salah, Ibrahim; Little, Richard S.; Santra, Dipak K.; Regassa, Teshome; Wang, Meng Yuan (Sustainability, 2011)
Our long-term goal is to develop wheat cultivars that will improve the profitability and competitiveness of organic producers in Nebraska and the Northern Great Plains. Our approach is to select in early generations for highly heritable traits that are needed for both organic and conventional production (another breeding goal), followed by a targeted organic breeding effort with testing at two organic locations (each in a different ecological region) beginning with the F6 generation. Yield analyses from replicated trials at two organic breeding sites and 7 conventional breeding sites from F6 through F12 nurseries revealed, using analyses of variance, biplots, and comparisons of selected lines that it is inappropriate to use data from conventional testing for making germplasm selections for organic production. Selecting and testing lines under organic production practices in different ecological regions was also needed and cultivar selections for organic production were different than those for conventional production. Modifications to this breeding protocol may include growing early generation bulks in an organic cropping system. In the future, our selection efforts should also focus on using state-of-the-art, non-transgenic breeding technologies (genomic selection, marker-assisted breeding, and high throughput phenotyping) to synergistically improve organic and conventional wheat breeding.